South American Childhoods Since the 1990s Between Neoliberalisation and the Expansion of Rights—An Introduction - Vergara-Del Solar, A (Palgrave Macmillan, 2021)
States in the South American region, with their predominantly authoritarian practices, increasingly discarded responsibility for social welfare as they embarked on processes of political and social democratisation. Yet during the 1990s, they found themselves required to become guarantors of the social rights of children, as well as of children’s rights to protection and participation. In this context, the emergence of a “universal child” creates a disputed territory about politics and moral governance that the introduction explores. It focuses, first, on the characteristics of neoliberalisation processes in Latin America; second, on the institutionalisation of children’s rights and third, the emergence or reconfiguration of the field of childhood studies. In discussing these topics, the introduction argues that South America has never been simply a region that has received and imported modernising influences from the countries of the North. It also raises the question of the nature of the “South American child”, a topic touched on throughout this book from different perspectives. © 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.